The dynamics of change in a privatised Polish state owned enterprise: An analysis of the human resource management implications - Izabela Robinson (Journal for East European Management Studies, 1999)
The move from a command to a market led economy in Poland has resulted in extensive political, economic and social change. Western multinational companies drive change in Eastern Europe and when Polish state owned enterprises are acquired by western multinationals this change process is accelerated. This paper explores the human resource management (HRM) issues arising from the acquisition of a Polish state owned enterprise by a western multinational and focuses on the use of four principal mechanisms to stimulate change namely, organisational re-structuring, the use of change agents, the re-deployment of key people and the dissemination of new cultural values and norms. It considers how these mechanisms have been used in the process of enabling the organisation to adapt to a changed environment and discusses the varying perceptions of those involved in the change process. – – Der Wechsel von der Plan- zur Marktwirtschaft in Polen führte zu weitreichenden politischen, wirtschaftlichen und sozialen Veränderungen. Multinationale Unternehmen aus dem Westen treiben die Veränderungen in Osteuropa voran und bei der Übernahme polnischer Staatsbetriebe durch solche Unternehmen beschleunigen sich die Veränderungen. In dieser Arbeit geht es darum, Fragen des Human Resource Managements zu erörtern, die bei einer solchen Übernahme entstehen. Hauptaugenmerk liegt dabei auf vier grundlegenden Veränderungsmechanismen: Restrukturierung der Organisation; Einsatz von change agents; Neuverteilung von Schlüsselpersonen; Einführung neuer kultureller Werte und Normen. Dabei geht es sowohl darum, wie diese Mechanismen zur Anpassung an eine neue Umgebung eingesetzt wurden, als auch darum, auf welch verschiedenartige Weise diese Mechanismen von den Beteiligten wahrgenommen wurden.
Keywords: 650